Effects of vacuum far infrared towards Aquilaria subintegra leaves: article - Abd Halim, Khairul Anwar; Alwi, Habsah (2017)
The application of far infrared radiation (FIR) to vacuum drying is interesting since FIR leads to higher drying rates and yields the dried product of better quality. In this work, the effect of far infrared radiation drying towards Aquilaria Subintegra leaves was investigated. Aquilaria Subintegra leaves with an initial weight of 50g were dried at various temperatures (40, 50 and 60oC) for 4 hours of drying time and the VFIR were set to -200 Mbar to apply vacuum condition. The results revealed that temperature had significant effects on the drying kinetics and various qualities of the Subintegra leaves in terms of moisture content analysis. The dried sample were grinded and were extracted with Ethanol solution to investigated existence of active ingredients in sample by using Soxhlet Extraction method. From the HPLC chromatogram result there were no detection of any antipyretic compound or active ingredients in the leaves.